Student Bedtimes, Academic Performance, and Health in a Residential High School. (August 2017) - Wernette, Maliah J.; Emory, Jan
Inadequate sleep among adolescents is considered an epidemic in the United States. Late night bedtimes could be an important factor in academic performance and health with consequences continuing throughout adulthood. The purpose of this study was to explore the relationships between late night bedtimes, academic performance (grade point average [GPA]), and utilization of health care (school nurse visits) in a residential high school. The data were collected from archival records for one academic semester. The statistical analysis employed the nonparametric Pearson's correlation coefficient ( r ) with the standard level of significance (α = .05). Positive and inverse linear relationships were found between bedtime and school nurse visits ( p < .00001) and bedtime and GPA ( p = .007). The findings suggest students' late night bedtimes may be related to increased school nurse visits and lower academic performance. Adolescent late night bedtimes may be an important consideration for academic success and maintaining health in residential high schools.